Phenology and fruit quality of Surinam cherry trees in orchards: training system and seedling growth environment - Ricardo Stefeni, Alberto; Wagner Júnior, Américo; da Rosa, Viviane; Alfonzo Garay, Igor; Bueno Ferreira, Maiara; Araújo Moreira Rocha, Matheus (Comunicata Scientiae, 2025)
Surinam cherry (Eugenia uniflora L.) is a fruit tree species native to Brazil that produces fruits with potential for food, cosmetic, and pharmaceutical industries. However, there is no technical information for growing Surinam cherry in orchards. The objective of this study was to evaluate the phenology and fruit quality of Surinam cherry trees grown from minicuttings, based on effects of shading during seedling formation and orchard training systems. The experiment was carried out at the Federal University of Technology of Paraná (UTFPR), from 2018 to 2021. A randomized block experimental design with four replications was used, in a 5×3 factorial arrangement, consisted of light intensities during seedling formation and orchard training systems, with varying experimental units according to the analyses. Surinam cherry trees showed differences in the beginning and range of flowering and fruit maturation according to the shading environment used for seedling formation and the orchard training system. The fruit quality of Surinam cherry trees grown from minicuttings was not affected by the analyzed factors.